PENGGUNAAN KREMATORIUM BAGI UMAT HINDU: SEBUAH IDENTIFIKASI KUANTITATIF - KENCANA, EKA N.; DEWI, DIAN PRAMESTI; SUKARSA, I KOMANG GDE (E-Jurnal Matematika; Vol 11 No 4 (2022), 2022)
A crematorium is a special place for cremation of dead. In recent years, the Hindu community in Bali has become accustomed to use crematorium for doing ngaben rituals. This study aims to know the determinant of Balinese to do ngaben at crematorium. The population was all Hindu communities in Bali, with a sample of 120 Hindu families who have doing ngaben at the crematorium. These respondents were chosen by applying snow-ball sampling. To find the underlying determinant(s), explanatory factor analysis was used. Data for this study is collected by surveying the respondents using self-administered questionaire on January to March 2022. The results justify there are four factors determine Hindu community in Bali has become accustomed to use crematorium for ngaben. These factors are (a) the quality of the crematorium service as the organizer of ngaben ceremony, (b) conformity of cremation ceremony with conventional cremation, (c) the family's trust and the absence of objections from the traditional village; (d) and consideration of the economic dimension. These factors able to explain the determinant of Hindu balinese people conducted ngaben at crematorium as much as 63 percent.